Long Non-Coding RNA GABPB1-AS1 Augments Malignancy of Glioma Cells by Sequestering MicroRNA-330 and Reinforcing the ZNF367/Cell Cycle Signaling Pathway - Li X (Dove Medical Press, 2021)
Xiulong Li,1 Hongfeng Wang2 1Department of Neurosurgery, Caoxian People’s Hospital, Heze, 274400, Shandong, People’s Republic of China; 2Department of Neurosurgery, Yantai Harbour Hospital, Yantai, 264000, Shandong, People’s Republic of ChinaCorrespondence: Hongfeng WangDepartment of Neurosurgery, Yantai Harbour Hospital, No. 100, Xingfu Road, Zhifu District, Yantai, 264000, Shandong, People’s Republic of ChinaTel/Fax +86-15762793079Email hfWang_9101@126.comBackground: Deregulation of long non-coding RNAs (lncRNAs) is frequently relevant to the malignant phenotypical changes. This study aimed to explore the role of lncRNA GABPB1-AS1 in the malignancy of glioma cells.Methods: Abnormally expressed genes in glioma were analyzed using a GEO GSE2223 dataset. Short hairpin (sh) RNA silencing of GABPB1-AS1 was introduced in glioma cells to explore its correlation with the proliferation, apoptosis, and invasiveness of cancer cells. The target transcripts of GABPB1-AS1 were predicted by bioinformatics analyses. MicroRNA (miR)-330 inhibition was additionally introduced in the glioma cells after GABPB1-AS1 knockdown for rescue experiments. Animal studies were performed by inducing xenograft tumors in nude mice.Results: GABPB1-AS1 was highly expressed in the glioma tissues and associated with advanced WHO grades. GABPB1-AS1 knockdown reduced proliferation and invasiveness of glioma cells in vitro and in vivo. miR-330 was a target transcript of GABPB1-AS1. miR-330 inhibition restored the malignancy of glioma cells. miR-330 directly bound to ZNF367. ZNF367 was highly expressed in glioma tissues and positively correlated with GABPB1-AS1 expression, and it was relevant to the cell cycle signaling pathway. Downregulation of GABPB1-AS1 reduced the expression of ZNF367 and reduced the levels of cell cycle-related proteins PCNA, CDC20, CDC7 and CCNA1 in cells.Conclusion: This study demonstrated that GABPB1-AS1 competitively bound to miR-330 and de-repressed ZNF367 expression, leading to activation of the cell cycle signaling pathway and the growth and metastasis of glioma cells.Keywords: glioma, lncRNA GABPB1-AS1, miR-330, ZNF367, cell cycle signaling pathway